Effect of socioeconomic and institutional factors and sustainable land management practices on soil fertility in smallholder farms in the Mahottari District, Nepal. (18th November 2021) - Chaudhary, Ashok Kumar; Pandit, Ram; Burton, Michael
Abstract: Soil fertility decline is a serious global problem, leading to a decline in crop yields and jeopardizing household food security, particularly in developing countries. This paper examines the impact of socioeconomic and institutional factors and the adoption of sustainable land management practices on soil fertility changes on farms between 2002 and 2018 in the Mahottari District of Nepal. A household survey among 184 smallholder farmers was conducted in 2018 to complement soil survey data collected in 2002. A seemingly unrelated regression model was used to estimate factors influencing soil fertility changes between the two periods. The results showed that soil organic matter (SOM), phosphorus (P), potassium (K), and soil pH increased, on average, by about 0.2%, 97 kg/ha, 4 kg/ha, and 0.5 scales, respectively, on the studied farms. The regression results indicated that extension visits and government support (free seedlings) had positive effects, while cooperative membership negatively affected soil fertility changes. Moreover, practicing fallow land use improved soil fertility changes on farms, while practicing conventional tillage using animals deteriorated soil fertility changes. The adoption of agroforestry practices positively affected changes in P and K and negatively affected SOM. Overall, this study highlighted the importance of institutional characteristics and sustainable land management practices to improve soil fertility. The policy implications of these findings for enhancing soil fertility on smallholder farms are: (1) increase the frequency of extension visits to share relevant information with farmers; and (2) incentivize farmers to adopt agroforestry and fallowing practices on their farms.